Roholtiella volcanica sp. nov., a New Species of Cyanobacteria from Kamchatkan Volcanic Soils - Lira A. Gaysina; Jeffrey R. Johansen; Aniket Saraf; Rezeda Z. Allaguvatova; Sagarika Pal; Prashant Singh (Diversity, 2022)
During a study of biodiversity of cyanobacteria in Gorely volcano soils (Kamchatka Peninsula), a strain of heterocytous, a false branching cyanobacterium with gradually tapered filaments, was isolated. Prominent features of the strain were purplish-grey trichomes and firm, distinct multilayered sheaths. Based on the results obtained from the morphological, ecological, and phylogenetic analysis using the 16S rRNA and 16S–23S ITS region, 16S–23S ITS secondary structure analysis, comparison of flanking regions of BoxB and V3 helices, and the p-distance between the 16S–23S ITS region, we describe our strain K7 as a novel species of the genus Roholtiella with the name Roholtiella volcanica sp. nov., in accordance with the International Code of Nomenclature for algae, fungi, and plants. This work continues the rapid expansion of the description of new taxa of cyanobacteria, and particularly demonstrates a coming phase in cyanobacterial taxonomy in which the discovery of new species in recently described genera rapidly increases our understanding of the diversity in this phylum.